Trans-Season Reliability of Physical Fitness Testing in Students of “Tourism” Speciality - Zanevskyy, Ihor; Labartkava, Kostiantyn (Physical Education Theory and Methodology, 2020)
The study purpose was to prepare a model of the trans-season reliability of physical fitness testing on the example of “Tourism” speciality students. Material and Methods. A total of 50 university first year bachelor’s students studying “Tourism” as a business service were involved in the physical fitness testing: 20 males with body mass 67.3±9.5 kg (M±SD) and body length 174.6±5.6 cm; and 30 females (body mass 59.6±7.3 kg, body length 163.9±5.2 cm). Monthly testing was conducted seven times from September to March using a complex test KONTREKS–2. Trans-season mean score reliability was evaluated within the intraclass correlation model. Results. Approximately 86% of the students were found to be on the average and higher levels and only nearly 5% − on the low level. Males showed significantly better state of the physical fitness than females (16.6%, p < 0.002) with 96.3% similarity of trends in scores between males and females during the trans-season study. A great variation within these samples was noticed, too; a corresponding part in the total variation was derived as 93.6%. A strong and high level significant correlation (r > 0.80, p < 0.001) was determined between all the seven monthly test-retest trans-season trials. Significant trans-season reliability on the excellent level was found for each of two gender samples (ICC > 0.95, p < 0.001). Deviations from mean values for seven monthly tests undertaken during the study period were not significant (chi-squared = 13.939, p = 0.834). Conclusions. A model of the trans-season reliability of physical fitness testing created on the example of the first year bachelor’s students of “Tourism” speciality showed its effectiveness and could be recommended for physical education of high school students.